Pengaruh Motivasi Kerja dan Komunikasi antar Karyawan Terhadap Produktivitas Kerja Karyawan di PT Wonokoyo Cabang Kabupaten Cianjur - Mutaqin, Yanwar Abdul; Rahwana, Kusuma Agdhi; Karmila, Mila (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2023)
This research aims to determine and analyze the influence of work motivation and communication between employees, both simultaneously and partially, on employee work productivity at PT. Wonokoyo Branch of Cianjur Regency. The method used in this research is quantitative with a descriptive approach. With a research sample of 42 employees as respondents. The data used is using primary and secondary data. The analytical tool used in this study is multiple linear regression using the SPSS version 20 support application. The results of research and hypothesis testing show that simultaneously there is a significant influence of work motivation and communication between employees on employee work productivity, as well as partial testing shows that there is a significant influence of work motivation and communication between employees on employee work productivity at PT. Wonokoyo Branch of Cianjur Regency.